Mapping the knowledge network of extracellular vesicles and angiogenesis in tumor-immune communication: a scientometric analysis - Wang, Kai; Lu, Dufu (Frontiers in Oncology, 2025)
ObjectiveThis study aims to explore the cooperative networks among authors, nations, organizations, and publications specializing in extracellular vesicle-angiogenesis, to evaluate the foundational knowledge, and to pinpoint future research directions and new topics.ApproachWe extracted all relevant articles from the Web of Science Core Collection (WoSCC) and reviews related to extracellular vesicle-angiogenesis published between January 1999 and December 2023, which met our inclusion criteria. We conducted author and keyword composition analyses using VOSviewer 1.6.18. Furthermore, we utilized Citespace 5.8 to analyze journals, institutions, countries, and keyword timezone maps to elucidate the knowledge network within this field.ResultsThe number of academic papers on extracellular vesicle-angiogenesis has steadily increased over the past 25 years. Researchers have closely collaborated globally, with 6,741 papers published in 4,393 academic journals across 111 countries or regions. Shanghai Jiao Tong University has the highest publication volume. Immunology and cancer are the primary focus areas, with Frontiers in Immunology and PLoS One being significant journals in this field. Cluster analysis results indicate that the relationship between extracellular vesicle-angiogenesis and tumors, inflammation, and regenerative medicine are the three main subfields in this domain. Current research hotspots include mesenchymal stem cells, exosomes, angiogenesis, circulating microRNAs, angiogenesis, and tumor microenvironment.ConclusionThis bibliometric study utilized visualization techniques to develop a knowledge map of extracellular vesicle-angiogenesis, revealing the significance of extracellular vesicles in tumor evasion by regulating intercellular communication between tumor cells and immune cells, and discussed the potential of exosomal biomarkers in precision medicine.